MUSIC FOR 13 MUSICIANS - Ardiansyah, Andika Renata; Mering, Aloysius; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMusic minmalism is one of the contemporary art that exist at this time. The music departs from an experimetal style with minimal concept but maximum result. That is, the concept of minimalism music in general only uses minimal processing patterns and then there is a change gradually and gradually so as to obtain  a complete musical composition. The autor tries to apply the technique in the work of minimalism music as a treatmen of harmony in his work. Formulation of the idea of creation of the work entitled ?Music for 13 Musician? was to apply aspect of musical work minimalism, toapply aspect of polytonal, and to apply multivalent aspect of musical instrumentation of Western and Indonesian traditions. The purpose of the work entitled ?Music for 13 Musician? was tohow to create ofminimalism music, to applypolytonal applied, and  to apply multivalent applied music intrumentation of Western and Indonesian traditions. The benefit of the work entitled ?Music for 13 Musician? is expected to be reference in music commposition learning.?Music for 13 Musician? is a form of minimalism musical composition involving the instruments of Indonesian tradition and Instrumens of Western tradition withminimalismmusical techniques process.  Keywords: music, minimalism, composition